Assessing The Efficiency of Web-Hosted E-Learning Platforms in Afghanistan Academic Settings: An Exploration at Herat University - Frishta Amiri; Tamanna Quraishi; Musawer Hakimi; Abdul Wajid Fazil (Lembaga Riset dan Inovasi Masyarakat Madani, 2024)
This study investigates the utilization and effectiveness of web-hosted e-learning platforms within the academic environment of Herat University. Adopting a quantitative research design, data were collected through a structured questionnaire administered to students and faculty members across various disciplines. The sample comprised 190 respondents from the Faculty of Medical, Education, Computer Science, Economics, and Law. Analysis involved descriptive statistics and chi-square tests using SPSS 26 software. Findings revealed diverse platform preferences, with HELMS emerging as the most commonly used platform. Overall, participants expressed high satisfaction levels with platform usability and perceived effectiveness in facilitating student engagement and interaction. Challenges related to cost, internet connectivity, and technical issues were identified, impacting the learning experience. Recommendations include enhancing platform usability through user-friendly interfaces and comprehensive training, as well as addressing technical and connectivity challenges. The study contributes to understanding the current landscape of e-learning at Herat University and provides insights for improving educational practices and policies.